Implementasi Sistem Pembangkit Listrik Tenaga Surya Di Taman Baca Masyarakat Istiqomah - Eka Dodi Suryanto; Marwan Affandi; Fahmy Syahputra; Ayu Elvana; Muchsin Harahap (Cattleya Darmaya Fortuna, 2025)
This activity describes the planning, installation, and evaluation of the implementation of a Solar Power Generation System (PLTS) at the Istiqomah Community Reading Park, Terjun Village, Medan Marelan District. The objectives of the activity are (1) to provide a reliable independent power supply for lighting and auxiliary learning devices at the reading park, (2) to increase the managers’ capabilities in operating and maintaining the PLTS, and (3) to assess the technical and social sustainability impacts after installation. Methods used include an energy needs and peak load survey, design of an off-grid system based on the survey results, installation of main components (PV panels, controller, batteries, inverter), and operational and maintenance training for the reading park managers. Evaluation was conducted through measurements of energy availability (hours of lighting operation), reduction in consumption from the PLN grid (kWh), and user satisfaction questionnaires. Based on the needs survey, the reading park’s electricity use is mostly allocated to lighting, fans, and computer operation. Results show that the installed PLTS successfully supplied 95% of the reading park’s daily electricity needs, directly resulting in monthly electricity savings of up to Rp 250.000,00. The results indicate that the designed PLTS meets lighting and light electronic device needs during the reading park’s operating hours, reduces dependence on external supply, and increases community participation in literacy activities, making it an effective strategy for achieving energy independence.